Experimental Systems: Future Knowledge in Artistic Research - Schwab, Michael (Leuven Leuven University Press, 2013)
Future Knowledge in Artistic ResearchThe experimental approach of science applied to artistic researchWe dont know what we dont know. This makes it difficult to imagine research that will produce truly new knowledge. In the sciences, the experimental approach has proved its worth in generating what subsequently requires understanding. Can the emergent field of artistic research be inspired by recent thinking about the history and workings of science? How can artists engage with experimentation to extend artistic values and deliver future knowledge?In this book fourteen contemporary artists, musicians, and theorists engage with Hans-Jörg Rheinbergers widely studied theory of experimental systems in an effort to determine how experimentation can productively be put to work in the arts. An interview with Rheinberger himself probes research as a potentially shared space between the otherwise different activities of art and science.ContributorsVirginia Anderson (Experimental Music Catalogue), Paulo de Assis (Orpheus Institute), Elke Bippus (Zurich University of the Arts), Henk Borgdorff (University of the Arts, The Hague, and University of Gothenburg), Darla M. Crispin (Orpheus Institute), Paolo Giudici (Royal College of Art, London), Gabriele Gramelsberger (Academy of Media Arts, Cologne), Peter Peters (Maastricht University and Research Centre Autonomy and the Public Sphere in the Arts, Zuyd Hogeschool, Maastricht), Hannes Rickli (Zurich University of the Arts), Michael Schwab (Royal College of Art, London, Zurich University in the Arts and Orpheus Institute Ghent), Stephen A. R. Scrivener (Chelsea College of Art and Design, London), Stefanie Stallschus (Independent Researcher), Neal White (Bournemouth University), Susanne Witzgall (Academy of Fine Arts, Munich)